Monitoring indicator genes to assess antimicrobial resistance contamination in phytoplankton and zooplankton communities from the English Channel and the North Sea - Bourdonnais, Erwan; Le Bris, Cédric; Brauge, Thomas; Midelet, Graziella (Frontiers in Microbiology, 2024)
Phytoplankton and zooplankton play a crucial role in marine ecosystems as the basis of the food webs but are also vulnerable to environmental pollutants. Among emerging pollutants, antimicrobial resistance (AMR) is a major public health problem encountered in all environmental compartments. However, the role of planktonic communities in its dissemination within the marine environment remains largely unexplored. In this study, we monitored four genes proposed as AMR indicators (tetA, blaTEM, sul1 and intI1) in phytoplankton and zooplankton samples collected in the English Channel and the North Sea. The indicator gene abundance was mapped to identify the potential sources of contamination. Correlation was assessed with environmental parameters to explore the potential factors influencing the abundance of AMR in the plankton samples. The prevalence in phytoplankton and zooplankton of sul1 and intI1, the most quantified indicator genes, ranged from 63 to 88%. A higher level of phytoplankton and zooplankton carrying these genes was observed near the French and English coasts in areas subjected to anthropogenic discharges from the lands but also far from the coasts. Correlation analysis demonstrated that water temperature, pH, dissolved oxygen and turbidity were correlated to the abundance of indicator genes associated with phytoplankton and zooplankton samples. In conclusion, the sul1 and intI1 genes would be suitable indicators for monitoring AMR contamination of the marine environment, either in phytoplankton and zooplankton communities or in seawater. This study fills a part of the gaps in knowledge about the AMR transport by marine phytoplankton and zooplankton, which may play a role in the transmission of resistance to humans through the marine food webs.